L. Frank Baum papers - Baum, L. Frank (Lyman Frank), 1856-1919.; Baum, L. Frank (Lyman Frank), 1856-1919.
Handwritten manuscript of Glinda of Oz with annotations (125 pages; published in 1920). Includes an undated autograph and note.
Author.
Collection material in English.
Keywords: American literature; Authors